Maxillary Swelling as the First Evidence of Multiple Myeloma. (12th November 2015) - Kasamatsu, Atsushi; Kimura, Yasushi; Tsujimura, Hideki; Kanazawa, Harusachi; Koide, Nao; Miyamoto, Isao; Endo-Sakamoto, Yosuke; Shiiba, Masashi; Tanzawa, Hideki; Uzawa, Katsuhiro
Abstract : Multiple myeloma is a malignant neoplasm of plasma cells characterized by proliferation of a single clone of abnormal immunoglobulin-secreting plasma cells. Since the amount of hemopoietic bone marrow is decreased in the maxilla, oral manifestations of multiple myeloma are less common in the maxilla than in the mandible. We report the case of 33-year-old Japanese man who presented with a mass in the right maxillary alveolar region. Computed tomography and magnetic resonance images showed a soft tissue mass in the right maxilla eroding the anterior and lateral walls of the maxillary sinus and extending into the buccal space. The biopsy results, imaging, and laboratory investigations led to the diagnosis of multiple myeloma. This case report suggests that oral surgeons and dentists should properly address oral manifestations as first indications of multiple myeloma.